창녕지역 축제에서 지역농특산물 및 그 가공품의 구매와 운영 프로그램과의 관련성 - 차용준; 허은실; Cha, Yong-Jun; Her, Eun Sil (Journal of the Korean Society of Food Culture, 2015)
This study analyzed purchasing characteristics of local agricultural products and processed products as well as evaluatedoperation programs for Changnyeon festival participants. The purchasing rates of local agricultural products and processedproducts at this festival were 63.6% and 49.1%, respectively, and the main purchased crops were onion (42.6%) and garlic(20.7%). Drinks (43.6%) were highly purchased processed products. The recognition (95.3%) and preferences (98.4%) forChangyeong local agricultural products were high at this festival. Subjects (72.5%) responded that public relations wereeffective for sale at this festival, and evaluation of the operation program for the festival was 3.51±0.74 (total score 5 points).Satisfaction with the experience event (37.7%) and exhibition event (33.6%) were high at this festival program, whereasparticipants gave low rates for art exhibition and sale events of local agricultural products (16.2%), cooking education(14.7%), direct education program (12.9%), and games (12.1%). This festival was an effective means of public relations,although purchase effects were not significant. This result suggests that the festival is necessary for planning a program toincrease purchasing.